2017
DOI: 10.1038/npp.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ibudilast on the Subjective, Reinforcing, and Analgesic Effects of Oxycodone in Recently Detoxified Adults with Opioid Dependence

Abstract: Ibudilast, a nonselective phosphodiesterase inhibitor, is used clinically in Asia for the treatment of asthma and poststroke dizziness. Recent preclinical studies have suggested that it also inhibits glial cell activation in rodents, and may alter opioid-mediated effects, including analgesia and withdrawal symptoms. The effects of ibudilast on the abuse potential of opioids in humans are largely unknown. The present study was designed to examine the influence of ibudilast on subjective (including drug craving)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…Metz and colleagues (Metz et al, 2017) extended these findings by testing the effects of ibudilast on the subjective and reinforcing effects of OXY. Non-treatment seeking opioid users (n=11) first underwent inpatient detoxification followed by maintenance on placebo (0 mg ibudilast, BID) and active ibudilast (50 mg, BID).…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 96%
“…Metz and colleagues (Metz et al, 2017) extended these findings by testing the effects of ibudilast on the subjective and reinforcing effects of OXY. Non-treatment seeking opioid users (n=11) first underwent inpatient detoxification followed by maintenance on placebo (0 mg ibudilast, BID) and active ibudilast (50 mg, BID).…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 96%
“…Recent studies have begun to investigate these medications in humans. A rigorous inpatient study among opioid-dependent subjects found ibudilast reduced opioid-seeking behavior and self-reported opioid craving, relative to placebo levels [15]. In separate studies, ibudilast reduced self-reported opioid withdrawal symptoms [254] and amplified oxycodone-induced analgesia [245] among opioid-dependent individuals.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Glial modulators, e.g. minocycline and ibudilast, may be effective medications for blocking the neuroimmune effects of abused substances [15, 245]. Minocycline is a tetracycline derivative that inhibits microglial activation and proliferation [246-248].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Recent studies show that the glial activation inhibitor ibudilast can decrease signs of withdrawal in opioid-dependent persons, and can also reduce the reinforcing effects of oxycodone [168,169]. …”
Section: Current Research Goalsmentioning
confidence: 99%